2011
DOI: 10.1128/jcm.02206-10
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of Epstein-Barr Virus and Cytomegalovirus from the Genital Tract of Women in a Periurban Community in Andhra Pradesh, India

Abstract: We found a large number of false-positive readings by visual inspection with acetic acid (VIA) in a study of cervical cancer screening strategies (VIA, human papillomavirus HPV DNA testing, and Pap cytology) in a periurban community in Andhra Pradesh, India. We evaluated whether these false-positive readings might be occurring as a result of infections with Epstein-Barr virus (EBV) or cytomegalovirus (CMV), prevalent latent herpesviruses known to be shed from the female genital tract. While we found that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 30 publications
7
25
1
1
Order By: Relevance
“…On the other side, the odds of having genital CMV were significantly higher among young women than in older women which is comparable to what was observed in previous studies [12,13]. In addition, in the current study as it was observed previously, young age at first sexual intercourse was significantly found to predict genital CMV infections [20].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…On the other side, the odds of having genital CMV were significantly higher among young women than in older women which is comparable to what was observed in previous studies [12,13]. In addition, in the current study as it was observed previously, young age at first sexual intercourse was significantly found to predict genital CMV infections [20].…”
Section: Discussionsupporting
confidence: 80%
“…In addition, this study has confirmed the association of genital CMV with low CD4 counts [12]. However; in contrast to previous report [13] genital CMV did not show any association with cervical inflammatory changes despite being significantly common in patients with low CD4+ counts (Figure 1). CMV has been found to cause different manifestations in HIV infected patients [14,15].…”
Section: Discussioncontrasting
confidence: 54%
“…According to some previous studies EBV infection is more frequent in older women, but CMV prevalence decreases with age (18,21). In our case EBV and CMV infections were found only in women older than 35 years.…”
Section: Discussionmentioning
confidence: 51%
“…While the role of EBV has been established in the aforementioned cancers, there is conflicting evidence regarding the role of EBV in cervical cancer . The prevalence of EBV infection was significantly higher in women with relatively higher grades of cervical disease among studies in India and Africa . Furthermore, both EBV encoding regions and EBV latent oncoproteins have been found in cervical tumor tissue .…”
Section: Introductionmentioning
confidence: 99%